Integrating digital marketing strategies and neuromarketing techniques for enhanced business performance - Yulduzkhon Abdullaeva, (THE INNOVATION ECONOMY, 2026)
The fast transformation of marketing from broad-based mass campaigns into accurate, data-driven strategies owes its existence to the rapid emergence of many new digital technologies. As neuromarketing has arisen, a frontier appears to invoke unconscious consumer responses, offering valuable insights into the emotional and cognitive processes that drive buying decisions. This paper discusses how digital marketing and neuromarketing strategy can be integrated to present the best possible effect, then emphasizes their synergy which will clearly lead to significantly heightened business outcomes. Within the purview of an exhaustive review of scholarly literature, models, theoretical and real case studies from around the world, it is shown that combining data with neurophysiological insights leads to marketing campaigns which are more steadfast and sound.